Di Balik Keyakinan: “Islam Fundamentalis” atau “Islam Neo-Modernis”? (Analisis Sosio-Historis Pemberitaan Majalah Tempo 1980-1994) - M. Deden Ridwan (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
This study explores how Tempo magazine reported on the Islamic “neo-fundamentalist” movement—specifically ḥarakah—and its positioning in relation to the discourse of “neo-modernist Islam” in Indonesia from 1980 to 1994. The latter movement, though not entirely synonymous, has later been associated with what is commonly referred to as “liberal Islam.” Tempo is considered to have had a significant influence in presenting and shaping these two intellectual currents through its journalistic coverage. By analyzing the magazine’s reporting, this study seeks to discern Tempo’s intellectual inclination between these two Islamic ideologies. The findings suggest that media outlets, to a certain extent, inherently possess and project an intellectual vision in their editorial stance.